IDENTIFICATION OF INTEFERENCE HV LINE PROTECTION IN PLGTU PT PJB GRESIK GENERATION UNIT USING METHOD RCFA AND FDT - Pranandari, Resti; Misbah,, Misbah,; Irawan, Deny (Jurusan Teknik Elektro Fakultas Teknik UNESA, 2021)
In the electricity generation business in Indonesia, power plants requiring to be reliable when operating and ready when needed due to network load requirements. It has been written in the performance target contract for each unit, therefore the protection system installed at the power plant must be well. The problem that occurs at the PLTGU PT PJB Gresik Generation Unit is a malfunction in the HV Line protection system that causes the generator unit to trip, thus causing questions regarding the cause of the problem that occurs. Therefore, the authors compile a thesis proposal with the title